متطلبات تطوير مؤسسة التجارة الخارجية في ظل المتغيرات الدولية المعاصرة - هرمز نور الدين; أبازيد ثناء; أصلان غياث (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر مؤسسة التجارة الخارجية إحدى أهم ركائز قطاع التجارة الخارجية، حيث يتم من خلالها استيراد كافة المواد والسلع الضرورية لكافة القطاعات الاقتصادية سواء الزراعية منها أو الصناعية فهي تُعنى بتنظيم شؤون الاستيراد والتصدير وتساهم بشكل كبير في تحقيق التنمية. لذلك كان لابد من دراسة متطلبات تطوير تلك المؤسسات من خلال التطرق لواقع مؤسسات التجارة الخارجية وأهميتها وكفاءتها والية عملها ومدى فاعلية إعادة هيكلة هذه المؤسسات ودمجها بمؤسسة واحدة، كما تم التطرق إلى مجموعة من الجوانب، ومن أهمها إستراتيجية الاستيراد والتصدير ودور القوى العاملة المؤهلة علمياً وفنياً وإدارياً في تنشيط الحركة التجارية، كما تم دراسة واقع مؤشر الربحية لهذه المؤسسات قبل عملية الدمج وبعده بهدف كشف الجوانب السلبية والعمل على إزالتها. Syrian foreign trade represents turning points in the course of the Syrian economy, since independence till the end of the twentieth century. After independence, the Syrian government tends to adopt an interior economic policy that upholds the potentials of support and protection from any foreign competition, in spite of the changes in the political regimes, aiming to achieve an economic atmosphere which provides developments requirements and fulfill the basic needs of the country. The Syrian government sought a variety of procedures, aiming to build an independent national economy, starting from the regulation of exportation and importation affairs through drafting licenses for import operation, encouraging the importation of rudimental materials and needed machines for agriculture and industry, in addition to panning industrial products importation which are locally produced. Moreover, the government sought cotton production. The foreign trade sector witnessed many collective agreements (Arab trade convention, Syrian-European cooperation treaty) and dual agreements which help in market expansion, and foreign and interior trade activation, consequently, production activity.